(untitled) (Bangladesh Journal of Medicine, 2024)
Opioid analgesics are essential in palliative care, providing significant pain relief for patients with advanced illnesses or at the end of life. These medications are administered via various routes, including oral, transdermal, subcutaneous, and intravenous, and doses are carefully adjusted to achieve optimal pain control while minimizing side effects such as constipation, nausea, sedation, and respiratory depression. Despite the risks, with proper monitoring, opioids can safely enhance patients’ quality of life in palliative care, complemented by psychosocial interventions to address holistic needs. Opioid rotation is a key strategy in managing pain when current opioids provide inadequate relief or cause intolerable side effects. This involves switching to an alternative opioid or adjusting the dose to optimize pain management while minimizing adverse effects. Successful opioid rotation requires careful assessment, monitoring, and collaboration among healthcare professionals. In Bangladesh, the opioid crisis differs from many Western countries, characterized by limited access to essential opioids like morphine rather than widespread abuse. Bureaucratic hurdles, lack of financial incentives for pharmaceutical companies, and insufficient demand due to "opiophobia" among physicians create significant barriers. Regulatory challenges, stigma, and limited availability result in inadequate pain relief for terminally ill patients, causing unnecessary suffering. Addressing these issues necessitates comprehensive strategies, including policy reforms to improve opioid access, education to combat stigma, and prioritizing palliative care within healthcare systems. Ensuring adequate access to opioids is crucial for upholding the dignity and comfort of those facing terminal illnesses, enabling them to receive the essential pain relief they deserve. Bangladesh J Medicine, 2024; Vol. 35, No. 2, Supplementation: 146-147